Improving Students' Speaking Ability in Expressing Opinion through Think Pair Share: English - Yohana Puspita Dewi (Journal of English Development, 2023)
A difficult speaking in English has become one of the student problems in English learing. The application of using Think Pair Share method is needed for students to improve students’ speaking ability in expressing opinion.. This is classroom action research which has purpose to describe whether think pair share method can improve students’ speaking ability in expressing opinion at eighth grade of SMPN1 Kotabumi. The research procedure consist of four steps, namely: planning, implementation, observation and reflection. Each cycle consist of two meetings and one assessment to measure students’ speaking ability in expressing opinion, each meeting lasted for 70 minutes. The second cycle was a remedial of the first cycle by revising some components that used in the learning process. To collect the data, the researcher use d oral test and observation sheet. The data is analyzed by summing the score and counting the percentage. The percentage is used as learning indicator that has been approved by the researcher and collaborator. The standart score of speaking is 70. If the targeted percerntage is reached 90% or more it means that the implementation of Think Pair Share method in expressing opinion said succeed. From the data analysis, the percentage of students’ activity in the first cycle is 72%, and it increases into 100% in the second cycle. Meanwhile, the teacher’s activity also increases from 75% in cycle 1 into 97,5% in cycle 2. So, it can be concluded that Think Pair Share method can improve students’ speaking ability in expressing opinion at eighth grade of SMPN 1 Kotabumi.